2011
DOI: 10.5851/kosfa.2011.31.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Concentration in Soybean Sauce on the Physicochemical Properties of Pre-rigor Ground Hanwoo Muscle

Abstract: This study was conducted to examine the effect of salt concentration in soybean sauce (ganjang) on pre-rigor ground Hanwoo (Korean native cattle) muscle. Although adding soybean sauce reduced pH of pre-rigor Hanwoo muscle, it improved the water holding capacity (WHC), cooking loss, total protein solubility, myofibrillar fragmentation index (MFI), 2-thiobarbituric acid (TBA) values, and textural properties by increasing salt concentration in the soybean sauce. In particular, adding soybean sauce inhibited lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This processing technique is based on the inactivation of endogenous enzymes involved in glycolysis at high ionic strength, which can in turn serve to minimize the decline in pH (Hamm, 1977 ; Kim et al, 2015 ). Thus, the effects of pre-rigor salting are greatly dependent upon the amount of salt added (Coon et al, 1983 ; Kim et al, 2011 ), and it has been suggested that the addition of at least 2% NaCl is required to guarantee the beneficial effects of pre-rigor salting on chicken breast (Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This processing technique is based on the inactivation of endogenous enzymes involved in glycolysis at high ionic strength, which can in turn serve to minimize the decline in pH (Hamm, 1977 ; Kim et al, 2015 ). Thus, the effects of pre-rigor salting are greatly dependent upon the amount of salt added (Coon et al, 1983 ; Kim et al, 2011 ), and it has been suggested that the addition of at least 2% NaCl is required to guarantee the beneficial effects of pre-rigor salting on chicken breast (Kim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the emulsion sausage containing above 3% of soy sauce showed significantly (p<0.05) decreased lightness (70.93) and redness (9.10) and increased yellowness (12.67) when compared to control (lightness, 72.01; redness, 9.67; and yellowness, 8.10). Similarly, Kim et al (22) reported the effect of soy sauce on color of pre-rigor ground beef. McGough et al (14) indicated that soy sauce affected both the internal and external color of frankfurter and determined that color impact was a critical point to be considered upon the application of soy sauce to frankfurter.…”
Section: Resultsmentioning
confidence: 94%
“…Marination increased the water-holding capacity (WHC) of the SMPL due to the salt content. Curing or marination partially solubilizes proteins, which increases the WHC (Kim et al, 2011). However, too long margination periods caused shrinkage and leakage of intracellular water in SMPL.…”
Section: Amino Type Nitrogen Myofibril Fragmentation Index (Mfi) and Cooking Lossmentioning
confidence: 99%